O que (não) dizem os números – para além das estatísticas sobre o Novo Mapa Religioso Brasileiro (The meaning of numbers - beyond statistics on the Brazilian New Religious Map). DOI: 10.5752/P.2175-5841.2011v9n23p690 - Passos, Mauro (Horizonte, 2011)
The article shows that within the Brazilian religious field new ways of believe have emerged. In this way, it also shows that some religions are in expansion – as some evangelical movements and traditional religions while some traditional religions – like Catholicism – are in a process of disenchantment. This article aims, from the 2009 Household Budget Survey – Pesquisa de Orçamentos Familiares (POF/IBGE, 2009) – data on religion published in a recent study elaborated by Fundação Getúlio Vargas (NERI, 2011), discuss the composition of this new religious map. Regarding the Christian churches, the FGV` study showed, in quantitative terms, the decrease in the number of Catholics, the stabilization of Pentecostal evangelicals’ percentage and the growth of non-Pentecostal evangelicals. Initially, based on the historical development of statistics on religion in Brazil, the numerical decline of Catholicism, its implications and perspectives will be analyzed. Basing on a critical analysis of the FGV’s study conclusions about the Brazilian protestant field numbers, the article will interpret the possibilities and limitations of using survey data for understanding the Brazilian religious field dynamics. In this way, the Brazilian religious landscape should be interpreted beyond the statistics